Efek Carbon Emissions Disclosure, Kinerja Lingkungan, Investment Opportunity Set, Profitabilitas & Ukuran Perusahaan terhadap Nilai Perusahaan (Studi pada Perusahaan Sektor Energi yang Terdaftar BEI 2020-2024) - Bonaventura Butar Butar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effect of Carbon Emission Disclosure (CED), environmental performance, Investment Opportunity Set (IOS), profitability, and firm size on firm value in energy sector companies. The research aims to provide academic insights and practical implications for investors, regulators, and companies in enhancing sustainability practices. A quantitative approach with purposive sampling was employed using data from annual reports, sustainability reports, and official publications of energy companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Firm value serves as the dependent variable, while CED, environmental performance, IOS, profitability, and firm size act as independent variables. Based on predetermined criteria, including sustainability reporting, carbon emission disclosure, financial data completeness, and PROPER participation, 138 observations were analyzed. The findings reveal that Carbon Emission Disclosure, environmental performance, and profitability positively and significantly influence firm value.